Amelioration of cognitive impairment using epigallocatechin-3-gallate in ovariectomized mice fed a high-fat diet involves remodeling with Prevotella and Bifidobacteriales - Qu, Yang; Wu, Yan; Cheng, Wei; Wang, Dongyang; Zeng, Lu; Wang, Yanru; Li, Tingting; Zhang, Liye; Yang, Jinan; Sun, Liyang; Ai, Jing (Frontiers in Pharmacology, 2023)
Background: Estrogen deficiency and a high-fat diet (HFD) are both risk factors for Alzheimer’s disease (AD). HFD can accelerate cognitive impairment in estrogen-deficient patients, but there is currently no effective treatment. Epigallocatechin-3-galate (EGCG) is widely studied for its anti-inflammatory, anti-cancer, and anti-neurodegeneration effects. Nevertheless, whether EGCG can ameliorate cognitive impairment in HFD-fed estrogen-deficient mice has not been studied. Methods and Results: Ovariectomized (OVX) mice fed an HFD (HFOVX) for 8 weeks experienced impaired object recognition and spatial memory, but this damage was significantly attenuated by the administration of EGCG at a dose of 45 mg/kg. Through 16S rRNA gene sequencing, we found that HFOVX changed the diversity and structure of the gut microbiota in mice, which could be restored with EGCG. Further analysis showed that HFOVX exposure not only resulted in a decrease of Alloprevotella in Bacteroidetes, Lactobacillaceae in Firmicutes, and Prevotella in Bacteroidetes but also in an increase of Bifidobacteriales in Actinobacteria. EGCG effectively reversed the decrease of Prevotella and inhibited the increase of Bifidobacteriales but had no effect on the decrease of Alloprevotella or Lactobacillaceae or on the increase of Enterorhabdus in HFOVX mice. Additionally, using Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, we found that EGCG significantly reversed the five functional gut microbiota genes elevated by HFOVX, including iron complex transport system substrate-binding protein, iron complex transport system permease protein, 3-oxoacyl- [acyl-carrier protein] reductase, transketolase, and 8-oxo-dGTP diphosphatase. Conclusions: We concluded that EGCG improved cognitive impairment in mice with estrogen deficiency exacerbated by an HFD involved a rebuilding of the disrupted gut microbiota composition.